The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1139/v90-226
|View full text |Cite
|
Sign up to set email alerts
|

Electronic effects of heterocyclic substituents. Spectroscopical and theoretical (AM1) study in a series of heterocyclic carboxaldehydes

Abstract: . The electronic effects of a series of 18 heterocyclic carboxaldehydes (furans, thiophenes, pyrroles, and pyridines) have been studied by means of the correlation existing between I3C chemical shifts of the carbonylic carbon and calculated total and T charges (AMI). The implications of this theoretical model to explain polar and resonance contributions to the total electronic effect are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Research on spectroscopic properties using this method have also been reported. 34 Certain drawbacks of AM1 are known however. The study of the water dimer has shown that AM1 predicts peculiar geometries for the equilibrium structure.…”
Section: Introductionmentioning
confidence: 99%
“…Research on spectroscopic properties using this method have also been reported. 34 Certain drawbacks of AM1 are known however. The study of the water dimer has shown that AM1 predicts peculiar geometries for the equilibrium structure.…”
Section: Introductionmentioning
confidence: 99%
“…3-Pyridyl substituents on the contrary are sterically much more accessible to be conjugated to platinum­(II) complexes in this porphyrin system while displaying the same benefits in terms of rotational freedom, leading to a smaller tendency of forming aggregates and therefore not lowering the effectivity of the PS. Additionally, 3-pyridyl substituents do not show an electron-withdrawing effect in comparison to 2-pyridyl and 4-pyridyl substituents due to a lack of resonance between the site of attachment to the remaining photochemical system and the nitrogen, which is expected to have an influence on the potency of the PS . Porphyrins containing four 3-pyridyl substituents conjugated to metal complexes have been reported to be more photosensitizing than their 4-pyridyl analogues at an equivalent degree of substitution while being more soluble and forming less aggregates in aqueous media .…”
Section: Resultsmentioning
confidence: 99%
“…81,82 Moreover, a similar competition between the intermolecular Nicholas reaction and intramolecular BF 3promoted O-cyclization has been reported. 83 In the case of indole, its higher donor ability compared to benzothiophene 84 promoted the cyclization of Co-complex 16 within the BF 3activated C 3 -triple bond instead of the Nicholas reaction. All attempts to synthesize a double Co-complex of enediyne 14 with both complexed triple bonds failed, even when fivefold excess of Co 2 (CO) 8 per one alkyne moiety was used: only the formation of monocomplexes 15 and 16 was detected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%